Pembelajaran Dengan Pendekatan Outing Class (Penelitian Fenomenologi di RA Al-Inshof Cibadak Lebak Banten Tahun 2024) - A, Asrowi (LPPM STAI La Tansa Mashiro, 2024)
This study analyzes the implementation of learning with the outing class approach at RA Al-Inshof Cibadak, Lebak, Banten in 2024 using a phenomenological approach. The research explores the experiences related to the implementation of outing class activities and their impact on early childhood development. The outing class activities, which involve visits to educational places such as zoos and parks, allow children to learn through observation and interaction with their surroundings. The results of the study indicate that outing class has a positive impact on the motor, social, and cognitive development of children. This experiential learning approach also enriches children's knowledge, enhances social skills, and strengthens their understanding of concepts taught in class. The findings highlight the significant potential of outing class in improving the quality of education and supporting early childhood development. Keywords: Learning, Outing Class.